The application of the method associate by training sessions on the subject «Art» (Journal of Educational Sciences, 2017)
The subject of the article is evaluation quality of one of types of students’ class assignments on the subject of «Art» – an associogram. The novelty of the academic approach of the article’s authors is that based on analysis of the meaning, types of associogramms and scientific data on hierarchical topology of quality of associations, determining content of associograms, science based criteria system of evaluation of students’ educational associaograms is proposed. The practical value of the researchis that the authors provide materials, required for a science based quality evaluation of associograms’ content within studying a school subject. The article includes descriptions of seven types of associograms, characteristics of four levels of associations and presents three basic evaluation criteria of associograms for learning session emphasized by authors. The types of asociogram: freecircular asociogram; dictionary snake; citation asociogram; asociogram-acrostic; cross-asociogram; asociogram «Double myself»; thinking activity map (MindMap), etc. The quality of asociogram is determined by the type of associations (local, narrowly system, intra-system, intersystem).
Keywords: evaluation; local association; private-system association; internal system association; intersystem association